The discursive dimension of development communication - Eligio, Anne-Marie Jennifer E. (The Philippine Journal of Development Communication, 2008)
This paper discusses the discursive dimension of development communication. The inspiration is derived from the author's doctoral dissertation, that had a two-fold interest: to render development communication with a meaning-making role and to derive a theoretical bent to understand issues of power in the policy asking process.